Elevated Serum Levels of Alpha-Fetoprotein in Patients with Infantile Hemangioma Are Not Derived from within the Tumor - Itinteang, Tinte; Chibnall, Alice M.; Marsh, Reginald; Dunne, Jonathan C.; de Jong, Sophie; Davis, Paul F.; Leadbitter, Philip; Tan, Swee T. (Frontiers in Surgery, 2016)
Aims: The embryonic-like stem cell origin of infantile hemangioma (IH) and the observed elevated serum levels of alpha-fetoprotein (AFP) in patients with hepatic IH led us to investigate if this tumor was the source of AFP. Materials and Methods: We measured serial serum levels of AFP in patients with problematic proliferating IH treated with surgical excision or propranolol treatment. We also investigated the expression of AFP in extra-hepatic IH samples using immunohistochemical staining, mass spectrometry, NanoString gene expression analysis and in situ hybridization. Results: Serum levels of AFP normalized following surgical excision or propranolol treatment. Multiple regression analysis for curve fittings revealed a different curve compared to reported normal values in the general populations. AFP was not detected in any of the IH samples examined at either the transcriptional or translational levels. Conclusion: This study demonstrates the association of proliferating IH with elevated serum levels of AFP which normalized following surgical excision or propranolol treatment. We have shown that IH is not the direct source of AFP. An interaction between the primitive mesoderm derived IH, and the endogenous endodermal tissues, such as liver, via an intermediary, may explain the elevated serum levels of AFP in infants with extra-hepatic IH.